Physiological Response and Comfort Sensory Perception towards Physical-Mechanical Performance of Compression Hosiery Textiles (Journal of Fiber Bioengineering and Informatics, 2018)
The purpose of the present study is to determine the psycho-physiological effects ofmechanical properties of compression hosieries (CHs) with different pressure levels and longitudinalgradient distribution profiles on the wearing comfort perception and blood circulation performanceof the lower extremities in vivo. The mechanical properties of CHs (tensile, shearing, and bending)significantly influencing pressure level performances have been instrumentally estimated. Bloodcirculation as the main physiological parameter was investigated along the long and short saphenousveins and popliteal veins (PopV) of a total of 24 lower extremities of twelve female subjects byusing Colour Doppler Ultrasound equipment in conjunction with four-hour subjective wear trials ina controlled environmental chamber. The study demonstrated that the mechanical properties of CHsfabric produced gradient variations along hosiery hose and among pressure levels. The skin pressuresapplied by CHs with four pressure levels significantly decreased the cross-sectional areas, andincreased the mean flow velocities (VP mean) of the PopV by 15.70%, 29.80%, 31.30 % and 24.20%,respectively. Wearing comfort and acceptance degree significantly correlated with mechanical qualityof CHs textiles. Light and mild compression by CHs provides the subjects more comfort sensoryperception for long-term wearing period. The application of CHs textiles appears to be effective inpreventing venous dilation and improving blood circulation in the lower extremities when wearers lackof physical activities. The fabrics with lower elasticity and higher bending rigidity properties producedhigher pressure; while no significant differences in increasing blood circulation was found amongmild, moderate, and strong pressure levels. An illustrative plot represents the integrative relationshipsbetween multiple materials mechanical properties, pressure performance, and resultant physiologicalresponses and subjective comfort sensory perception, which provide a reference for product designerand physician in development and application of functional compression hosiery textiles.